2022
DOI: 10.1158/1078-0432.ccr-22-1281
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib Rechallenge for Hormone Receptor–Positive/HER-Negative Advanced Breast Cancer: Findings from the Phase II BioPER Trial

Abstract: Purpose: To assess the efficacy and exploratory biomarkers of continuing palbociclib plus endocrine therapy (ET) beyond progression on prior palbociclib-based regimen in patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-) advanced breast cancer (ABC). Patients and Methods: The multicenter, open-label, phase II BioPER trial included women who had experienced progressive disease (PD) after having achieved clinical benefit on the immediately prior palbociclib plus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…While the BioPER study was a single arm trial not designed to show superiority, and cross-trial comparisons should be taken with a grain of salt, the mPFS seen here (3.2 months) is comparable to control arms (fulvestrant alone) of other 2L ET trials (5,7,8). Similarly, the PACE study (16) was not able to show superiority of the continuation of palbociclib beyond first progression (versus fulvestrant alone), raising the possibility that patients progressing on 1L palbociclib may have developed resistance to the drug, although in PACE, there was a suggestion that patients with tumors harboring ESR1 mutations may continue to derive some benefit from palbociclib, again limited by the small numbers, and in direct conflict with the resistance signature presented in the current article (14). The larger, randomized phase 2 PALMIRA trial (NCT03809988) will try to answer the question of clinical benefit of continuing palbociclib in 198 patients who have progressed on palbociclib plus an AI after deriving clinical benefit from it.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…While the BioPER study was a single arm trial not designed to show superiority, and cross-trial comparisons should be taken with a grain of salt, the mPFS seen here (3.2 months) is comparable to control arms (fulvestrant alone) of other 2L ET trials (5,7,8). Similarly, the PACE study (16) was not able to show superiority of the continuation of palbociclib beyond first progression (versus fulvestrant alone), raising the possibility that patients progressing on 1L palbociclib may have developed resistance to the drug, although in PACE, there was a suggestion that patients with tumors harboring ESR1 mutations may continue to derive some benefit from palbociclib, again limited by the small numbers, and in direct conflict with the resistance signature presented in the current article (14). The larger, randomized phase 2 PALMIRA trial (NCT03809988) will try to answer the question of clinical benefit of continuing palbociclib in 198 patients who have progressed on palbociclib plus an AI after deriving clinical benefit from it.…”
mentioning
confidence: 75%
“…Recent observational data (13) suggests potential benefit of continuing CDK4/6 blockade beyond progression on CDK4/6i therapy. In the January 1 st , 2023 issue of Clinical Cancer Research, Albanell et al (14) reported data from the phase 2 BioPER trial, which had the co-primary objectives of estimating clinical benefit from continuation of palbociclib beyond progression as well as exploring potential biomarkers of clinical benefit. This small single arm study included 33 patients with ER + /HER2 − mBC who progressed on immediately prior palbociclib plus ET after having achieved clinical benefit on it (response or stable disease ≥24 weeks).…”
mentioning
confidence: 99%
“…The high level of HER2-enriched lesions might be due to the more aggressive features of metastatic disease and endocrine treatment-refractory disease potentially losing its luminal features after disease progression 40 . Furthermore, in the recent BioPER trial, after treatment with a CDK4/CDK6 inhibitor, 37.5% of the samples showed a HER2-enriched subtype 53 , suggesting that HER2-enriched tumors are prominent in patients that are heavily pretreated and/or that have been exposed to CDK4/CDK6 inhibition, as was the case for 94% of ER + GELATO patients. Interestingly, in GELATO, 90% of primary tumors were classified as either luminal A or luminal B (Supplementary Table 4), suggestive of an acquired HER2-enriched phenotype later in the disease course.…”
Section: Discussionmentioning
confidence: 98%
“…The phase II BioPER single-arm study enrolled 33 patients with advanced ER+/HER2-breast cancer who had prior clinical benefit to but subsequently progressed on palbociclib plus ET ( Albanell et al, 2023 ). Patients continued palbociclib but had switch of their ET.…”
Section: Therapeutic Strategies Following Progression On Cdk4/6 Inhib...mentioning
confidence: 99%
“…Clinical benefit rate was 34% and median PFS was 2.6 months ( Albanell et al, 2023 ). A composite biomarker signature incorporating low Rb score (defined as <1% tumor cells with positive nuclear staining on immunohistochemistry), high cyclin E1 (defined as ≥10% tumor cells with positive nuclear staining on immunohistochemistry), and ESR1 mutation was associated with poorer PFS ( Albanell et al, 2023 ). Other trials evaluating continued CDK4/6 inhibition are in progress and included in Supplementary Table S2 .…”
Section: Therapeutic Strategies Following Progression On Cdk4/6 Inhib...mentioning
confidence: 99%